Osmanlı-Türk düşüncesinde münazara ilmi ve Abdünnafi İffet’in Tercüme-i Adab-ı Gelenbevi adlı eseri - Kömbe, İlker (My University, 2004)
Âdâbu'l-bahs ve'l-münâzara ilmi, küllî bir tartışma teorisi olup, mantık ilmiyle doğrudan bir ilişkiye sahiptir. Bunun yanında, cedel ilmi vasıtasıyla kelâm, hilâf ilmi vasıtasıyla da fıkıh usûlü ilimleriyle bağlantıları vardır. Münâzara ilmi Osmanlı medrese sisteminde ve eğitim programında merkezî bir yere sahiptir. Bu yer sebebiyle, medreselerin özellikle, orta (iktisad) ve yukarı (istiksa) seviyeleri tahlil (analiz) ve tenkid (kritik) kriterlerine göre organize edilmiştir. Âdâbu'l-bahs ve'l-münâzara ilmi, Osmanlı toprakları dışında kurulmasına rağmen, en yoğun ve en canlı özelliğini Osmanlı döneminde elde etmiştir. Bu bağlamda, Tercüme-i Âdâb-ı Gelenbevî adlı eser, münâzara ilminin Osmanlı düşüncesindeki seviyesini göstermesi açısından, en önemli metinlerden birisidir.

The science called Munazara in Islamic thought is an universal theory of disputation. There is a direct relationship between this general theory of disputation and logic. Also, this universal theory of disputation has a connection with theology by means of dialectic (cedel) that is important for theological dispute and jurisprudence by means of juridical dispute called hilâf in Islamic thought. This general theory of disputation had a central position in the system of Ottoman madrasa and educational programs. Because of this central position, especially middle (iktisad) and high (istiksa) levels of madrasas was based on analysis and critic as main criterions (criterias). Although universal theory of disputation is established outside of Ottoman lands. The studies about this theory transformed into vigorous and dominant character in Ottoman period. In this context, the book called Tercüme-i Âdâb-ı Gelenbevî and written by Abdunnâfi İffet Efendi is one of the most important texts that indicate the high level of this theory in Ottoman-Turkish thought.
Keywords: Felsefe, İslam